Investigation of Ion Temperature Characteristics in the HT-7 Tokamak - 李颖颖 符佳 石跃江 王福地 张伟 提昂 许平 黄懿赟 胡纯栋 DNB team (Plasma science & technology, 2011)
Characteristics of ion temperature measured with charge-exchange recombination spectroscopy （CXRS） were studied in Ohmic, lower-hybrid-wave （LHW） driven and ion-cyclotron- resonance-frequency （ICRF） heated plasmas in HT-7. The results indicate that the central ion temperature T10 follows the one-third power law in the product of central line-averaged density Ne and plasma current Ip in Ohmic discharges and is therefore consistent with the Artsimovich scaling law T10 = K （Ip Bt ne R2）1/3. It is shown that there is an appreciable increase of ion temperature during the operation with both LHW and ICRF and that the increment of ion temperature in those shots is mainly due to the energy transfer via collisions between ions and electrons rather that by direct heating of the ions.